Uji Hedonik dan Daya Simpan Sediaan Salep Ekstrak Etanol Umbi Hati Tanah - Nurul Qamariah; Rezqi Handayani; Ahmad Irza Mahendra (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
The Tanah Hati plant is one of the medicinal plants that have benefits as traditional medicine and is used by the people of the city of Palangka Raya, Central Kalimantan Province. Empirically this plant tuber is believed to treat wounds, postpartum wounds, malaria, and diarrhea. The ethanol extract of the Hati Tanah tuber has been made into an innovative pharmaceutical preparation in the form of an ointment. Hati Tanah tuber ethanol extract ointment is intended to inhibit wound infection caused by the bacteria Staphylococcus aureus. The purpose of this study was to determine the level of preference through hedonic tests and shelf-life stability of pharmaceutical preparations of ethanol extract ointment from Hati Tanah tuber with a hydrocarbon base and a water-soluble base. The method used in this study is a method non-experimental with steps in the form of hedonic tests and shelf-life stability. The assessment that becomes a reference in the hedonic test includes aroma, shape, and color. To test the stability with the shelf-life indicator using the variable storage time after the measured variable. The stability test was carried out for 2 weeks, tested from day 0 to day 14 by observing changes in aroma, shape, and color of the ethanol extract of the liver soil tuber ointment. Based on the results of research that has been carried out on 20 panelists and 2 weeks of storage, it was found that the pharmaceutical preparations of the ethanol extract of the liver tuber in a water-soluble base were preferred in terms of aroma and shape. Meanwhile, the preparation of hydrocarbon-based ointments is preferred in terms of the color of the preparation. In the shelf-life stability test, it was found that the pharmaceutical preparations of the ointment with ethanol extract of the liver tubers on a hydrocarbon basis showed a change in the dosage form on the 7th day, which was watery at the top of the ointment. While the water-soluble base ointment remained stable for 2 weeks of storage.